Knowledge about Antibiotic Use amongst the Public: a cross sectional study in Karachi - Saima Naseem; Iffat, Wajiha; Shakeel, Sadia; Tariq, Syed Areeb Bin (Infectious Diseases Journal of Pakistan, 2023)
Background: Antibiotic resistance is a major public health problem globally. Its main contributing factor is inappropriate use of antibiotics. This practice is highly prevalent in developing countries. There is need of effective interventions to curtail the irrational consumption of antibiotics. The present study evaluated knowledge, attitude and practices of people of Karachi towards antibiotic use in order to devise suitable educational campaigns. Method: A Cross-sectional study was done from January 2015 to August 2015 using self-administered questionnaire regarding antibiotic use. The study was carried out on non- medical professionals. All completely filled questionnaires were entered into SPSS version 20.00 and analyzed. Descriptive statistic on sample characteristics was computed in percentages. Results: A total of 600 participants completed the questionnaire. Majority of the participants had poor knowledge of antibiotics and selfmedicate without physician’s consultation. More than half (67%) of the respondents thought that antibiotics could cure all infections. Sixty five percent believed that antibiotics could treat viral infections as well. A significant number of the participants (45.17%) purchased antibiotics without doctor’s prescription and many of them kept its stock at home for emergency purposes. Half of the participants 49.17% used antibiotics prescribed to any member of their family. Majority of the respondents were interested in attending educational programs on effective antibiotic use. Conclusion: The results of the study reveal the lack of awareness regarding appropriate antibiotic consumption. It is necessary to introduce short training programs on rational antibiotic use. Moreover there must be control on the purchase of antibiotics without the prescriptions by physicians. Keywords: Antibiotic, antibiotic resistance, self-medication